Myotoxin II from Bothrops asper (Terciopelo) venom is a lysine-49 phospholipase A2 - Francis, Brian (1991)
A basic, dimeric myotoxic protein, myotoxin II, purified from Bothrops asper venom has a similar molecular weight and is immunologically cross-reactive with antibodies raised to previously isolated B. asper phospholipases A2, except that it shows only 0.1% of the phospholipase activity against L-alpha-phosphatidylcholine in the presence of Triton X-100. Its 121 amino acid sequence, determined by automated Edman degradation, clearly identifies it as a Lys-49 phospholipase A2. Key amino acid differences between myotoxin II and phospholipase active proteins in the Ca2(+)-binding loop region, include Lys for Asp-49, Asn for Tyr-28, and Leu for Gly-32. The latter substitution has not previously been seen in Lys-49 proteins. Other substitutions near the amino terminus (Leu for Phe-5 and Gln for several different amino acids at position 11) may prove useful for identifying other Lys-49 proteins in viperid and crotalid venoms. Myotoxin II shows greater sequence identity with other Lys-49 proteins from different snake venoms (Agkistrodon piscivorus piscivorus, Bothrops atrox, and Trimeresurus flavoviridis) than with another phospholipase A2 active Asp-49 molecule isolated from the same B. asper venom. This work demonstrates that phospholipase activity per se, is not required in phospholipase molecules for either myotoxicity or edema inducing activities.